Natural law and political realism in the history of political thought - Dyson, R.W. (New York, 2005)
This is the first volume of a detailed history of the traditions of natural law and political realism in western political thought. It elucidates the ways in which the relation between politics and morality was understood by major thinkers from classical antiquity to the Renaissance. Emphasis is given not only to the exegesis of texts, but to the intellectual and historical contexts in which those texts must be read if they are to be properly understood. The second volume continues the analysis through the twenty-first century and addresses the question of whether the modern (S0(Bnatural law(S1 (Brhetoric of human rights can be given a respectable philosophical basis. This two-volume set is a valuable resource for scholars working in the fields of history, international relations, philosophy, and politics.s
volume I : from the Sophists to Machiavelli
Keywords: Political science-Philosophy